ضمانات تنفيذ الأحكام القضائية الإدارية - سديرة, الحبيب; ليحيو, محمد (University of Eloued جامعة الوادي, 2022)
And what we conclude with this memorandum, the Algerian legislator was able to develop clear and updated legal texts that take into account the peculiarities of the Algerian judicial system and what was decided by the jurisprudence of the administrative chamber of the former Supreme Court. The State Consultative Council, as well as what he quoted from the comparative laws, in order to fill the void that existed in the old Civil Procedures Law. With regard to the conditions that must be met in the judicial ruling being implemented, the Algerian legislator has introduced new articles related to the procedures for notifying judicial rulings, especially those submitted to the administration, as well as the executive formula related to the law. Issuance of an administrative court ruling against the administration. It granted the judge the powers of urgency, and was able to fill the void related to suspending the implementation of administrative judicial decisions. It should be noted the impossibility of requesting the execution of the judgment issued against the administration that is exempted from any obligation to implement according to the conditions stipulated in the Civil and Administrative Procedures Law mentioned above, but here by the will of the State Council. And not with its unilateral will, which is considered an exception to the original, and in all cases, the good faith of the administration is required and without arbitrariness from it.وما نخمز إليو مغ خلاؿ ىحه السحكخة، فإف السذخع الج ا دئخؼ قج استصاع أف يزع نرػص قانػنية واضحة مدتحجثة مع م ا خعاة خرػصيات الشطا القزائي الج ا دئخؼ وما استقخ عميو الاجتياد القزائي لمغخفة الإدارية بالسحكسة العميا سابقا ومجمذ الجولة، وكحلظ ما أقتبدو مغ القػانيغ السقارنة، وذلظ لدج الف ا خغ الحؼ كاف مػجػد في قانػف الإج ا خءات السجنية القجيع فبالشدبة لمذخوط الػاجب تػفخىا في الحكع القزائي محل التشفيح، فالسذخع الج ا دئخؼ استحجث مػاد ججيجة متعمقة بإج ا خءات تبميغ الأحكا القزائية خاصة مشيا التي تبمغ للإدارة، وكحلظ الريغة التشفيحية الستعمقة بالحكع القزائي الإدارؼ الرادر ضج الإدارة، والسذخع لع يتجاوز مدألة وقف تشفيح الق ا خر الإدارؼ وىػ مغ مػاضيع القزاء الإستعجالي، فقج مشح لقاضى الإستعجاؿ سمصات، وتسكغ مغ سج الف ا خغ الستعمق بػقف تشفيح الق ا خ ا رت القزائية الإدارية والسلاحع أنو يدتحيل شمب تشفيح الحكع ضج الإدارة التي تتحخر مغ أؼ الت ا د بالتشفيح شبقا لمحالات السشرػص عمييا في قانػف الإج ا خءات السجنية والإدارية السحكػرة سالفا، لكغ ىشا بإ ا ردة مغ مجمذ الجولة وليذ بإ ا ردتيا السشفخدة، وىػ ما يعتبخ كاستثشاء عغ الأصل، وعمى كل حاؿ يذتخط حدغ نية الإدارة ودوف تعدف مشيا.
مدكرة ماستر
Keywords: : administrative court rulings, threat of fine, management directive orders, administrative judge; الأحكا القزائية الإدارية، الغ ا خمة التيجيجية، ت ػجيو أوامخ لملإدارة، القاضي الإدارؼ.